The Possibility of Talaq Performers Criminalization in Indonesia: An Essential Lesson from India - Suryani, Irma; Budia Warman, Arifki; Roni Efendi; Tenrilawa , Dian Furqani (Journal of Human Rights, Culture and Legal System, 2024)
The absence of sanctions against instant triple talaq and out-of-court divorce in Indonesia presents significant challenges for justice on gender equality and women's rights in today’s modern society. This study has the primary objective of analyzing the issues surrounding talaq divorce regulations in Indonesia by reflecting on the regulations in India. The study employs a combination of normative legal research methods, a legislative approach, and a comparative approach, focusing primarily on the marriage laws of Indonesia and India. The findings indicate that the practice of ‘triple talaq’ or instant divorce in India has been banned, with criminal sanctions imposed, including a three-year imprisonment for violators. In contrast, the regulations on talaq in Indonesia remain administrative in nature, requiring individuals to perform talaq in court, with no sanctions established for those who violate the regulations. The lack of criminal sanctions for talaq in Indonesia stems from its dual legal system and the absence of comprehensive guidelines on the procedural aspects of talaq, compounded by the limited resources of religious courts. In addition, the social stigma attached to divorce further complicates the issue. In India, the imposition of criminal sanctions for triple talaq aims to challenge the rigidity of the law and prioritize the rights of women and children. The reconstruction of regulations on divorce can be achieved through three components of criminal sanctions, comprising legal substance, legal structure, and legal culture. Also, it is essential to take humanitarian considerations and local wisdom in Indonesia into account when implementing such criminal sanctions.